Women who kill men : California courts, gender, and the press - Bakken, Gordon Morris (Law in the American West., 2009)
The late nineteenth and early twentieth centuries were a revolutionary period in the lives of women, and the shifting perceptions of women and their role in society were equally apparent in the courtroom. Women Who Kill Men examines eighteen sensational cases of women on trial for murder from 1870 to 1958.